2012
DOI: 10.1186/1471-2296-13-115
|View full text |Cite
|
Sign up to set email alerts
|

The CareWell-primary care program: design of a cluster controlled trial and process evaluation of a complex intervention targeting community-dwelling frail elderly

Abstract: BackgroundWith increasing age and longevity, the rising number of frail elders with complex and numerous health-related needs demands a coordinated health care delivery system integrating cure, care and welfare. Studies on the effectiveness of such comprehensive chronic care models targeting frail elders show inconclusive results. The CareWell-primary care program is a complex intervention targeting community-dwelling frail elderly people, that aims to prevent functional decline, improve quality of life, and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 37 publications
(43 reference statements)
0
16
0
4
Order By: Relevance
“…18,19 Details were published previously. 20 The study was reviewed by the ethics committee of the Radboud University Medical Centre Nijmegen (registration no. 2010/403) and registered at ClinicalTrials.gov (identifier NCT01499797).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…18,19 Details were published previously. 20 The study was reviewed by the ethics committee of the Radboud University Medical Centre Nijmegen (registration no. 2010/403) and registered at ClinicalTrials.gov (identifier NCT01499797).…”
Section: Methodsmentioning
confidence: 99%
“…Extended information on the sample size calculation was published in the study protocol. 20 Statistical Analysis Outcomes at the participants' level were analyzed with linear mixed-model analyses to account for the clustering of participants within the GP practices. Outcome estimates were corrected for significant differences in baseline characteristics that correlated with the primary outcome, and for the baseline value of the outcome (in the case of secondary outcomes) by including these variables as covariates.…”
Section: Sample Size Calculationmentioning
confidence: 99%
“…Information provided about the exact content of the instrument varied between CGAs. For five CGA instruments, the content of the CGA was available in (the appendix of) the original study or in a study cited in the original study (Buurman et al, ; Buurman, Parlevliet, van Deelen, de Haan, & de Rooij, ; Fleischer et al, ; Ruikes et al, , ; Stijnen, Duimel‐Peeters, et al, ; Suijker et al, , ). For the other CGAs, the original study did not provide or only partially provided the exact content of the CGA nor referred to other papers describing this information.…”
Section: Resultsmentioning
confidence: 99%
“…Three CGA instruments were tested for their validity and reliability (De Stampa et al, ; Ruikes et al, , ; Van Hout et al, ; Vedel et al, ). For four CGAs, it was explicitly indicated that the instrument was tested for its feasibility (Daniels et al, ; Metzelthin, van Rossum, de Witte, Hendriks, & Kempen, ; Metzelthin et al, ; Ruikes et al, , ; Stijnen, Duimel‐Peeters, et al, ; Suijker et al, , ). For nine CGAs, the average duration of conducting the assessment was described, which ranged from 30 min to 3 hr.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation